Two‐Photon Photoemission Spectroscopy for Studying Energetics and Electron Dynamics at Semiconductor Interfaces. Issue 8 (3rd April 2019) - Friedrich, Dennis; Sippel, Philipp; Supplie, Oliver; Hannappel, Thomas; Eichberger, Rainer
Abstract : Time‐resolved two‐photon photoemission spectroscopy (tr‐2PPE) directly probes the kinetic energy and dynamics of photoemitted electrons. At the same time, the electronic structure and temporal occupation of surface‐near states can be accessed, which allows to unravel the fundamental processes governing electron dynamics and energetics in semiconductor surfaces. Here, recent studies on epitaxial III–V semiconductors and II–VI nanostructures are reviewed and the feasibility to study electron dynamics in III–V surface quantum wells (SQW) with tr‐2PPE is demonstrated. On InP(100), for example, surface states are filled by electrons relaxing from higher energetic bulk states. In the case of nanostructured materials, these effects play an even larger role due to the high surface to bulk ratio. For CdSe quantum dots, Auger recombination strongly competes with the exploitation of the quantum size dependent phonon bottleneck. The electron cooling dynamics in CdSe platelets are extremely fast and exhibit complete independence of Auger‐like processes. Finally, an InGaAs SQW/InP structure is shown to exhibit much longer lifetime of the quantum confined states. The SQW may act as a carrier accumulation layer for bulk electrons diffusing to the surface. Implications for future use in energy material systems for photovoltaic and photocatalytic applications are discussed. Abstract : Time‐resolved two‐photon photoemission spectroscopy (tr‐2PPE) is a powerful experimental method to simultaneously unravel the energetics and dynamics of photoexcited electrons at semiconductor interfaces. This topical review covers recent studies on epitaxial III–V semiconductors and II–VI nanostructures and it demonstrates the feasibility to study electron dynamics in III–V surface quantum wells. Implications for future use in energy material systems are discussed.